Economic analysis of antenatal screening for human T-cell lymphotropic virus type 1 in Brazil: an open access cost-utility model. Issue 5 (May 2023) - Rosadas, Carolina; Senna, Kátia; da Costa, Milene; Assone, Tatiane; Casseb, Jorge; Nukui, Youko; Cook, Lucy; Mariano, Lívia; Galvão Castro, Bernardo; Rios Grassi, Maria Fernanda; Penalva de Oliveira, Augusto Cesar; Caterino-de-Araujo, Adele; et al.
Summary: Background: Human T-cell lymphotropic virus type 1 (HTLV-1) is a retrovirus that causes severe diseases, such as aggressive cancer or progressive neurological disease. HTLV-1 affects mainly people in areas with low human development index and can be transmitted from mother to child, primarily through breastfeeding. Refraining from breastfeeding is an effective intervention to reduce the risk of infection in infants. However, HTLV-1 antenatal screening is not offered globally. According to WHO, the scarcity of cost-effectiveness studies is considered one of the major barriers to the implementation of policies to prevent HTLV-1 infection. Therefore, this study aimed to assess the cost-effectiveness of antenatal screening and postnatal interventions to prevent HTLV-1 mother-to-child transmission in Brazil and to develop an open-access, editable, mathematical model that can be used by other countries and regions to assess different scenarios. Methods: In this cost-utility analysis, we constructed a decision tree and a Markov model to assess the cost-effectiveness of HTLV-1 antenatal screening and postnatal interventions (ie, avoidance of breastfeeding, by suppression of lactation with cabergoline, and provision of formula feed) to reduce transmission. For our model, we used data from Brazil and we took the perspective of the public health-care system to estimate costs. Findings: The implementation of both screening and interventions would result in the prevention of 1039 infections in infants every year in Brazil with an incremental cost-effectiveness ratio (ICER) of US$11 415 per quality-adjusted life-year (QALY). 88% of all probabilistic sensitivity analysis simulations had ICER values lower than the Brazilian cost-effectiveness threshold ($18 107·74 per QALY). HTLV-1 prevalence in pregnant women, the risk of HTLV-1 transmission when breastfeeding lasts for 6 months or more, and the cost of screening tests were the variables with the largest effect on ICER. Interpretation: HTLV-1 antenatal screening is cost-effective in Brazil. An open-access model was developed, and this tool could be used to assess the cost-effectiveness of such policy globally, favouring the implementation of interventions to prevent HTLV-1 mother-to-child transmission worldwide. Funding: None. Translations: For the Portuguese and Spanish translations of the abstract see Supplementary Materials section.